2015
DOI: 10.1016/j.ebiom.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model That Reproduces the Developmental Pathways and Site Specificity of the Cancers Associated With the Human BRCA1 Mutation Carrier State

Abstract: Predisposition to breast and extrauterine Müllerian carcinomas in BRCA1 mutation carriers is due to a combination of cell-autonomous consequences of BRCA1 inactivation on cell cycle homeostasis superimposed on cell-nonautonomous hormonal factors magnified by the effects of BRCA1 mutations on hormonal changes associated with the menstrual cycle. We used the Müllerian inhibiting substance type 2 receptor (Mis2r) promoter and a truncated form of the Follicle stimulating hormone receptor (Fshr) promoter to introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In particular, several mouse models were created by genetically manipulating murine oviductal cells [5862]. Some of these models have recapitulated the development of tubal precursor lesions [58,60] and demonstrated that salpingectomy blocks tumor development [58,61].…”
Section: Pathogenesis Of Epithelial Ovarian Cancermentioning
confidence: 99%
“…In particular, several mouse models were created by genetically manipulating murine oviductal cells [5862]. Some of these models have recapitulated the development of tubal precursor lesions [58,60] and demonstrated that salpingectomy blocks tumor development [58,61].…”
Section: Pathogenesis Of Epithelial Ovarian Cancermentioning
confidence: 99%
“…Published work documents that disruption of Trp53 frequently occurs in breast cancers that develop in women carrying BRCA1 mutations (18), contributes to cancer generation in mice with disrupted Brca1 alleles (12,14,19,30), and by itself does not lead to mammary cancer by age 12 months (16). Like Brca1 fl11/fl11/Cre/p53−/+ mice, Brca1 WT/fl11/Cre/p53−/+ mice developed invasive mammary cancer by age 12 months without significant difference in latency (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here we tested the impact of antihormonals on preneoplasia development with both one and two Brca1 alleles and found evidence of increased responsiveness to tamoxifen in Brca1 WT/fl11/Cre/p53−/+ as compared to Brca1 fl11/fl11/Cre/p53−/+ mice. There has been significant discussion around whether or not Brca1 LOH is required for cancer development (18,19). Significantly we determined that Brca1 LOH was not required for mammary cancer development and found no evidence that Trp53 LOH was required for cancer development even though this has been previously reported for this model (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chain of events can lead to spontaneous malignant transformation and, in fact, led to the establishment of immortal cell lines in our laboratory. 10 We hypothesize, based on observations not only with this in vitro model, but also with mice carrying a conditional Brca1 knockout 16 as well as observations with human populations, 17,18 that the molecular events mediating predisposition to triple negative breast carcinoma and high-grade serous extra-uterine Müllerian carcinoma in BRCA1 mutation carriers entail an interplay between cell-nonautonomous consequences of this carrier state in ovarian granulosa cells resulting in increased cellular proliferation and, thus, premature aging in mammary and extra-uterine Müllerian epithelia, and cellautonomous consequences leading to numerical chromosomal abnormalities in these epithelia due to cytokinesis failure associated with advanced replicative ages. 14 We sought to better understand the mechanism underlying the prolonged arrest at the spindle assembly checkpoint associated with increased replicative age, which is a central element of this proposed interplay between cell-autonomous and -nonautonomous mechanisms of cancer predisposition, in an effort to gain insights into the molecular events associated with early cancer development in individuals with germline BRCA1 mutations.…”
Section: Introductionmentioning
confidence: 99%